Effect of gonadotrophin releasing hormone on reproductive performance and steroid profile of postpartum suckled Surti buffaloes* - SHAH, R G; KHARADI, V B; DHAMI, A J; DESAI, P M; KAVANI, F S (The Indian Journal of Animal Sciences, 2014)
he effect of GnRH (250 µg im) on postpartum Surti buffaloes with smooth inactive ovaries till day 40 was studied on 6 animals, and 5 were kept as control. Blood plasma profiles of P4 and E 2-1713 were estimated by standard RIA procedures. The reproductive performance and ovarian events recorded with the help of rectal palpation findings were correlated to p4 and E2 profiles. Significanlly higher progesterone levels were observed in the GnRH treated than the control buffaloes on 9-10 weeks (2.78±0.71 vs 0.87±0.49 ng/ml) and 11-12 weeks (2.86±0.83 vs 1.04±0.52 ng/ml) postpartum. The plasma E,17 β levels following GnRH treatment increased for variable periods with a typical profile in 3 buffaloes folloWed by oestrus. GnRH treated buffaloes resumed ovarian activity on day 45.83±0.30 postpartum in contrast to day 64.00±2.27 in 4 untreated buffaloes. The occurrence of first heat postpartum in GnRH treated vs control group was 54.83±2.18 vs 96.75±14.39 days (P<0.05). The Treatment to ovulation interval in 5 of 6 treated buffaloes was 15.40±2.58 days with an overall mean of 19.00±4.16 days. All GnRH treated buffaloes conceived by 80 days postpartum. Of them. 33% buffaloes conceived within 60 days and 67% between 61-80 days postpartum. In control group, conception rate before day 60. 61, 80, 81-90 and 121-150 postpartum was 0,20,20 and 20% respectively. The remaining 40% control buffaloes conceived after 370 days postpartum. Thus, GaRH treatment has a good therapeutic action to initiare early ovarian activity and to enhance reproductive efficiency in Surti buffaloes.